Examination of Actuarial Offender-Based Prediction Assessments in Texas, 1993-1996 - Connolly, Michele M. ([Verlag nicht ermittelbar], 2008)
The purpose of this study was to provide a comprehensive assessment of the usefulness and effectiveness of prediction and classification of offenders under community supervision. A felony cohort data collection instrument was developed to test the validity of the Wisconsin Risk and Need Instrument in use in Texas, as well as to develop "better" predictor variables for a variety of dependent variables. Using the felony cohort data instrument, the Texas Department of Criminal Justice Community Justice Assistance Division (TDCJ-CJAD) collected detailed statewide information on 3,405 felony offenders placed on probation in Texas during October 1993. Specifically, the form was completed by a probation officer on all felony probation intakes at the time the initial case classification risk/needs assessment was conducted. Additionally, follow-up forms were developed and administered to track the offenders' progress at one year, two years, and three years. Variables include probationer information, current offense, criminal history, social history, substance abuse, probation sanctions, case classification risk items, and case classification need items. Additional variables include felony cohort one-year follow-up data form questions, felony cohort second-year follow-up data form questions, and felony cohort third-year follow-up data form questions.